Severe pregnancy-associated atypical hemolytic uremia syndrome in the context of the COVID-19 pandemic: a novel survival case report - Yan Yang; Xiao-jin Li; Hua-Yan Yuan; Jing-Jing Xiong; Peng-Fei Li; Zhen Wang (BMC Pregnancy and Childbirth)
Abstract Background Pregnancy-associated atypical hemolytic uremic syndrome (aHUS) is a form of thrombotic microangiopathy (TMA) caused by uncontrolled activation of the complement system during pregnancy or the postpartum period. In the intensive care unit, aHUS must be differentiated from sepsis-related multiple organ dysfunction, thrombotic thrombocytopenic purpura (TTP), hemolysis, elevated liver enzymes, and low platelet (HELLP) syndrome. Early recognition of aHUS is critical for effective treatment and improved prognosis. Although tests such as the ADAMTS13 level, peripheral blood smears, complement testing, and blood cultures are useful for diagnosing aHUS, these tests are time-consuming and may not be widely available. This report describes a case of severe aHUS in a pregnant woman during the coronavirus disease 2019 (COVID-19) pandemic. Case presentation A 26-year-old patient with a history of four pregnancies and one delivery (P4G1) presented at 30 weeks and 2 days of gestation with vaginal fluid leakage and fetal growth restriction detected by ultrasound at a different hospital. During labor induction, the patient developed a high fever and coagulopathy, followed by heart failure, acute kidney injury, anemia, and severe thrombocytopenia. The patient remained alert and coherent, with no evidence of neurological dysfunction. She was transferred to our department and was given invasive respiratory support, blood transfusion, continuous renal replacement therapy, capacity management, and other comprehensive treatments. Due to the ongoing COVID-19 pandemic, ADAMTS13 testing and complement inhibitor therapy were unavailable. A diagnosis of pregnancy-associated aHUS was made based on the patient's history, clinical presentation, and standard laboratory results. The patient was prescribed 13 sessions of hemodialysis. Post-treatment evaluation showed normalized complement C3 and C4 levels, stabilized platelet and hemoglobin levels, and gradual normalization of liver function. Renal function improved gradually, and a bone marrow biopsy revealed no fragmented red blood cells. The patient was transferred to the Department of Nephrology on day 40 and back to the local hospital on day 42. The patient was followed up for 3 years, during which her renal function returned to normal, with no recurrence of thrombocytopenia or microangiopathic hemolytic anemia. Conclusions This case highlights the challenges and importance of diagnosing and managing pregnancy-associated aHUS and multiple organ failure in a low-resource setting.